PENGARUH FAKTOR INSENTIF DAN MOTIVASI TERHADAP PRESTASI KERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN BENGKALIS - Gatot Wijayanto; Arini Novalinda (Jurnal Ilmiah Infokam, 2015)
The objectives of this research are to analyze and investigate the incentive factor and employee benefits of echelon III and IV employees at the government of Bengkalis with overall test and individual test. The research method used is verifycatve and the population in this research are 504 employees with esselonering back ground. By using a proporsional stratified random sampling method it has been obtained 50 respondents. Data collected with field and library study by using observation, interview and quetionnaires. Multiple Regression Analysis is used to determine relationship and influence of variable and in order to test the hypothesis, statistical analysis is used. The result of research shows that multiple correlation coefficient (R) valued at 0,8950 with probability (p) 0,05 and determination coeffcient value (R2) is 80,11%. It means that 80,11% factor incentive toward job performance of echelon III and IV at the government of Bengkalis. It indicated from the value of Fobs is larger than Ftable at the level of  = 5%. (Fobs = 94,656 Ftable = 3,195 with probability (p) = 0,000E+00 smaller than 0,05). From the figures, in the hypothesis nol is rejected meaning the factor incentive and employee benefits have been ralationship an influence of significant toward job performance of echelon III and IV employees at the government of Bengkalis. A partially (individual test) shows that the value of tobs the biggest on employees benefits variable, tobs = 13,196 ttable = 1,678 with a partial determination coefficient value (r2) = 78,74% and p = 0,00000. This result indicates that the employee benefits factor has most dominant relationship and influence on job performance of echelon III and IV employees at the government of Bengkalis.